Peran Penyuluh Pada Kelompok Tani “Palemboyan” Di Desa Taraitak Satu Kecamatan Langowan Utara Kebupaten Minahasa - Mokalu, Asyer Gabriel; Sendow, Martha Mareyke; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
This research aims to determine the perceptions of members of the "Palemboyan" farmer group regarding the role of Extension Officers in farmer groups. This research was conducted from March to May 2023 at Taraitak Satu Village, Langowan Sub-district, Minahasa District, Sulawesi Utara Province. This research was carried out using the data sampling method purposive sampling or intentionally. This research is in descriptive quantitative form with variable data calculated using the scoring method. The method used to compile the data is using a Likert scale through tabulation. The results of the research show that the perception of the role of instructors in the "Pelemboyan" farmer group in Taraitak Satu Village, North Langowan District, Minahasa Regency, results in the level of the role of instructors as motivators reaching 35 percent with the criteria of Less Role, the role of instructors as catalysts reaching 32.5 percent with the criteria of Less Role. , the role of instructors as organizers reached 32.5 percent with the criteria of Less Role, the role of instructors as communicators reached 37.5 percent with the criteria of Less Role and the role of instructors as advisors reached 35 percent with the criteria of Less Role.